Analisis Manajemen Risiko Reputasi pada Pondok Pesantren Al Khoziny Buduran Sidoarjo pasca Runtuhnya Bangunan Mushola dengan Pendekatan ISO 31000 - Novie Andriani Zakariya; Ameliya, Walida; Fatimatus Zahro; Yuliana Rahmawati; Yuslim Fadel Abdillah; Sesarea Ula Winaya; Muhammad Firdan Chazim; Muhammad Riky Ramadhani (Journal of Islamic Management, 2026)
This study discusses the reputation risk management of the Al-Khoziny Islamic Boarding School regarding the news of the collapse of the prayer room building (case study of the Al-Khoziny Islamic Boarding School in Buduran, Sidoarjo). This study aims to analyze and identify aspects of reputational risk that arise due to the incident, strategies that can be carried out to improve public perception and restore public trust. This study uses a qualitative method, using a case study approach involving interviews with victims of the collapse, guardians of students, the surrounding community and evacuation officers, with reference to the ISO 31000 guidelines as a guide in the risk assessment and management process. The results of discussion indicate that reputation can be negatively impacted when negative information spreads faster than official clarification, especially through digital media. To reduce and anticipate bad reputation, institutions must provide a quick response, transparency and empathetic public communication.